A KARAKTERISTIK KIMIA DAN ORGANOLEPTIK SET YOGURT BUAH CAMPOLEH (POUTERIA CAMPECHIANA) DENGAN VARIASI KONSENTRASI STARTER: Karakteristik Kimia dan Organoleptik Set Yogurt Buah Campoleh (Pouteria Campechiana) dengan Variasi Konsentrasi Starter - Veti, Veti Agustina Panca Kusnadi; Fizriani, Atia; Tubagus, Robi (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
Starter concentration is an important factor that influences the yoghurt set fermentation process. Development of a yogurt set with the addition of campolay fruit to enrich the taste, texture and increase the nutritional components. This research aims to determine the influence of chemical and organoleptic characteristics and to find the best treatment for the Campolay fruit yogurt set. This research uses a completely randomized design (CRD) method consisting of 4 treatments, namely 5%, 10%, 15%, 20% and repeated three times. . The research results showed that adding variations in starter concentration to the yogurt set had a significant effect on the parameters of protein, lactic acid and fat levels. However, it has no real effect on vitamin C, ash content, water content, and organoleptic values on taste, aroma, appearance, color and overall attributes. The best yogurt starter set concentration variation treatment was 5% (P1), which had an ash content of 0.87%, lactic acid 0.40%, protein content 5.27%, fat content 2.18%, vitamin C content 3,450mg /100g, color attribute 2.52(like), aroma attribute 2.68(like), taste attribute 2.64(like), appearance attribute 2.60(like) and overall 2.84(like).